2009
DOI: 10.1016/j.ijdevneu.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of high lipid and high energy diet on serum lipid, brain fatty acid composition, and memory and learning ability in mice

Abstract: A long-term high lard diet increased offspring serum TC and LDL-C levels and affected the brain's fatty acid composition, and memory and learning ability. The polyunsaturated fatty acid content of the brain may be correlated with serum cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 36 publications
2
42
2
Order By: Relevance
“…9 ). acid content correlated with maternal serum LDL-C levels ( 11 ). In this present study, in the absence of maternal obesity induced by HLE diet, the adult male offspring also showed higher serum cholesterol and lower nonfasting serum insulin levels.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…9 ). acid content correlated with maternal serum LDL-C levels ( 11 ). In this present study, in the absence of maternal obesity induced by HLE diet, the adult male offspring also showed higher serum cholesterol and lower nonfasting serum insulin levels.…”
Section: Discussionsupporting
confidence: 63%
“…After 1 week, 15 male and 15 female mice were transferred to one cage and fed the control diet [chow diet (CD)] or a high-lipid high-energy (HLE) diet (composed of 84% CD, 15.8% lard fat, and 0.2% cholesterol). These diets were used in one of our previous studies ( 11 ). Two days later, pregnant female mice were individually housed in cages.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional Mediterranean-style diet has fewer meats and carbohydrates and more plant-based foods and monounsaturated fat than a typical American diet. Following the traditional Mediterranean-style diet may lower incidence and prevalence of learning and memory functions [40,41] . In this regard, correlational studies have confirmed that polyphenols contribute to the prevention and treatment of learning and memory impairment [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…When 16-month-old rats were fed diets high in fat and cholesterol they made more errors in a test of working memory especially when memory loads were high, and they also showed altered hippocampal morphology (60). Similar studies of mice showed that high-fat diets worsen performance in learning and memory tests (49,181). There is some evidence that the effects of obesity on neuroplasticity and cognitive function differ in males and females.…”
Section: Animal Studiesmentioning
confidence: 98%